Canine Rabies: Significance and Threats - Singh, CK (Asian Journal of Biological and Life Sciences, 2012)
Rabies is an acute viral disease that infects domestic and wild animals and is transmissible to humans. Worldwide, rabies kills over 55,000 people every year. If there is any one species that can be pin pointed as the key species responsible for rabies perpetuation particularly in the developing world, it is canine particularly dog. The presence and involvement of dogs in man's life has become so interwoven and mutually dependent that has lead to increased possibilities of contact and exposure to rabies from dogs to man irrespective of the fact whether the dog is domesticated or stray. Dog has to be identified as the key species for focus of all control measures especially in the developing world. If rabies is eliminated from domestic animals and wildlife, the incidence of rabies in mankind will also be controlled.